Study on the fluidity, mechanical and fracture behavior of ABS/TPU/CNT nanocomposites. (August 2021) - Heidari, Farshad; Aghalari, Milad; Tehran, Ata Chalabi; Shelesh-Nezhad, Karim
Acrylonitrile butadiene styrene has relatively good mechanical performances, but its low melt fluidity limits the production of thin parts. In this research, acrylonitrile butadiene styrene/thermoplastic polyurethane (ABS/TPU) blends and ABS/TPU/CNT nanocomposites were prepared by employing melt-mixing process. The melt fluidity, mechanical and fracture behavior of different samples were evaluated. The morphology of fracture surfaces was studied by scanning electron microscopy. The addition of TPU into ABS substantially elevated the melt flow index, but noticeably weakened the notched impact toughness. The presence of carbon nanotubes in ABS/TPU blend promoted the mechanical performances and developed a rough fracture surface morphology. The notched impact resistance and essential work of fracture in nanocomposite containing 0.1 wt.% CNT showed about 95 and 50% increases respectively as compared to ABS/TPU (90/10) blend. In the presence of 0.3 wt.% CNT, the plane stress condition favorably dominated the toughness behavior, enhancing the non-essential work of fracture and crack propagation energy. The appropriate dispersion of carbon nanotubes and their adhesion to ABS/TPU polymer matrix were considered as the prominent factors affecting the fracture resistance of ABS/TPU/CNT nanocomposites.